SETTLEMENT OF DEFAULT IN THE CAR RENTAL AGREEMENT AT PT. SURYADITA 88 TRANSPORT IN BADUNG REGENCY - I Gusti Ngurah Made Siwa Mertayasa; Dewa Gede Pradnyana Yustiawan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Car rental businesses are now relatively accessible in Badung Regency. Because Badung Regency is a popular tourist destination, numerous individuals have opened car rental services. In Badung Regency, PT Suryadita 88 Transport is one of companies that offers car rental services. In its operation, PT Suryadita 88 Transport is not exempt from issues involving default-causing factors and efforts to resolve defaults. This study aims to uncover the causes of default in the car rental agreement at PT. Suryadita 88 Transport and potential solutions. This study employs the Empirical Law research technique, which correlates the legal aspects of existing issues with their practical application in society. The applicable legal basis is Article 1548 of the Civil Code, pertaining to Leasing. The results revealed that disputes shall be resolved through litigation if they cannot be resolved through alternative mean.